Landscape Controls on Water‐Energy‐Carbon Fluxes Across Different Ecosystems During the North American Monsoon - Perez Ruiz, Eli Rafael (2021)
The dependence of arid and semiarid ecosystems on seasonal rainfall is not well understood when sites have access to groundwater. Gradients in terrain conditions in northwest México can help explore this dependence as different ecosystems experience rainfall during the North American monsoon (NAM), but can have variations in groundwater access as well as in soil and microclimatic conditions that depend on elevation. In this study, we analyze water-energy-carbon fluxes from eddy covariance (EC) systems deployed at three sites: a subtropical scrubland, a riparian mesquite woodland, and a mountain oak savanna to identify the relative roles of soil and microclimatic conditions and groundwater access. We place datasets during the NAM season of 2017 into a wider context using previous EC measurements, nearby rainfall data, and remotely-sensed products. We then characterize differences in soil, vegetation, and meteorological variables; latent and sensible heat fluxes; and carbon budget components. We find that lower elevation ecosystems exhibited an intense and short greening period leading to a net carbon release, while the high elevation ecosystem showed an extensive water use strategy with delayed greening of longer duration leading to net carbon uptake during the NAM. Access to groundwater appears to reduce the dependence of deep-rooted riparian trees at low elevation and mountain trees on seasonal rainfall, allowing for a lower water use efficiency as compared to subtropical scrublands sustained by water in shallow soils. Thus, a transition from intensive to extensive water use strategies can be expected where there is reliable access to groundwater.